The Role of Knowledge Organization in Scientific Communication An Overview on JCR's Psychology Journals Guidelines about Title, Abstract and Keywords - Terra, Ana Lúcia (2020)
The aim of this exploratory study on writing the title, abstract and keywords of articles was to verify and analyze guidelines or strict rules for authors in scientific journals in the field of Psychology. A combination of quantitative and qualitative techniques has been used in a representative sample of journals in Psychology indexed in the Journal Citation Reports (JCR), considering the first eight titles of each of the four quartiles. The sample consisted of 32 journals out of 77 (41.5%). A previously adapted and tested spreadsheet has been used. The data collection and processing of 38 items were grouped into categories related to identification data, guidelines for the title, abstract and keywords of the scientific article. The results obtained reveal that the 32 journal titles belong to 11 different editors; all of them have some kind of style manual with orientations that vary between deep and more superficial; and most of them have guidelines for writing the title (75%, n. 24), abstract (96.8%, n. 31) and keywords (71.8% n. 23). The use of a graphic summary and a video summary stand out as new ways of disseminating the content of scientific articles. It is concluded that these aspects are aligned to a greater or lesser extent with the guidelines of the ISO Standard and the APA Manual. However, they are more related to the protocols of editorial management procedures for the dissemination of scientific work in a digital environment than to the intrinsic quality of documentary products associated with the organization and representation of science.